Hacia el centro: el PT y el gobierno de Lula en Brasil - Gonçalves Couto, Cláudio (Facultad de Ciencia Política y Relaciones Internacionales, Universidad Nacional de Rosario, 2010)
El gobierno de Lula representó la culminación de un proceso de circulación de elites en Brasil: llegó al poder nacional con un conjunto de liderazgos oriundos de los sectores hasta entonces excluidos del acceso directo al gobierno del país. Además, se consolidó una bipolarización partidaria centrista, con el PT a la centro-izquierda y el PSDB al centro, pero atrayendo los sectores sociales más conservadores, privados de una derecha partidaria capaz de representarlos en las disputas del gobierno nacional.

Lula’s administration represented the ultimate step of a process of circulation of elites in Brazil: the national power was gathered by a group of leaders who came from the social sectors historically excluded from the direct access to the country’s government. In addition, it was consolidated a centrist bipolarization between PT and PSDB, the former at the center-to-the-left and the last one at the center, however attracting the most conservative social sectors who were deprived of a partisan right that was capable of represent them in the national government political contests.
Towards the centre: PT and Lula’s government in Brazil
Keywords: Política brasileña; Sistema de partidos; Izquierda y derecha; Gobierno de Lula; Brazilian politics; Party system; Left and right; Lula’s administration